Analisis Karakteristik Wisatawan Lokal Pantai Mliwis, Kabupaten Kebumen - Dheanita Sekarini Octanisa; Andrea Basworo Palestho (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research was conducted at Mliwis Beach, Ambal, Kebumen Regency with 100 respondents local tourists. The purpose of this study is to test the characteristics of local tourists by using 6 characteristic categories namely gender, age, education, occupation, mode of transportation and information sources and then the data is processed using SPSS Version 26. The results of this study are the characteristics of tourists with gender categories dominated by female tourists by 58% with the majority of tourists aged 20-30 years at 47%, having a high school education level of 62%, having a private employee job by 38%, using private vehicles such as two- or four-wheeled vehicles to reach tourist destinations by 73% and getting information from close friends before 50%. The results of the research can contribute to strategy of tourism promotion by knowing the needs of tourists.